Emotional intelligence: new ability or renowned traits? An investigation of the convergent, discriminant and incremental validity - Wan Husin, Wan Nurul Izza (2017)
Despite the recent popularity of the concept of emotional intelligence, several researchers question current emotional intelligence tests on several grounds including their lack of construct validity and unstable factor structure. This thesis aims to investigate the construct validity of emotional intelligence. In particular, the present study seeks to (1) confirm the factorial validity of emotional intelligence, (2) examine the convergent validity between a performance-based test and self-report measure of emotional intelligence, (3) investigate the convergent validity between emotional intelligence and cognitive intelligence, (4) confirm the place of emotional intelligence in the “general cognitive intelligence” taxonomy, (5) measure the discriminant validity of emotional intelligence when correlated with personality traits, and finally, (6 and 7) assess the incremental validity of emotional intelligence, as measured by a performance-based test, over cognitive intelligence, personality traits, a self-report measure of emotional intelligence, and trait emotional intelligence in predicting [6] leadership practices and [7] positive interpersonal relationships. To achieve these aims, a conceptual framework is developed in line with the concept of ability-based emotional intelligence. As the present study is quantitative in nature, statistical tools such as Rasch measurement model, Structural Equation Modelling and SPSS are employed to test the proposed hypotheses. Data were collected from 710 undergraduate students registered at a public Malaysian University. The findings revealed that: (1) the four-factor structure of ability-based emotional intelligence construct can be deemed construct valid, (2) there is no convergent validity between performance-based and self-report measure of emotional intelligence (3) there is no convergent validity between emotional intelligence and cognitive intelligence, (4) ability-based emotional intelligence has no place in the intelligence taxonomy, (5) there is a discriminant validity between emotional intelligence and personality, and finally, (6 and 7) emotional intelligence (performance-based measure) exhibits incremental validity in predicting [6] the leadership practices and [7] the positive interpersonal relationships, while controlling for personality traits, self-reported emotional intelligence, and trait emotional intelligence. The implications of these findings are synthesized in terms of the existing literature and the prevailing conceptual framework set out at the beginning of this research, which could shape the direction for future research on the emotional intelligence construct.